A randomised crossover trial comparing nasal masks with oronasal masks: No differences in therapeutic pressures or residual apnea‐hypopnea indices. (29th August 2018) - Shirlaw, Teresa; Duce, Brett; Milosavljevic, Jasmina; Hanssen, Kevin; Hukins, Craig
Abstract: In treating obstructive sleep apnea (OSA), the use of oronasal masks with continuous positive airway pressure (CPAP) has been reported to increase pressure levels and reduce compliance. These reports come mostly from large observational studies. In this study, we examined the impact that oronasal masks have on 95th centile pressures, the residual apnea‐hypopnea index (AHI) and compliance compared with nasal masks. A randomised crossover design was implemented. Participants already established on CPAP were randomly allocated to a nasal mask or oronasal mask with auto‐titrating positive airway pressure (APAP) for 2 weeks. Participants then crossed over to use the alternate mask for another 2 weeks. Seventy‐one participants were recruited but only 60 completed the trial. There were no differences in median 95th centile pressure (nasal, 11.5 cm H2 O; oronasal, 11.7 cm H2 O; p  = 0.115), median residual AHI (nasal, 4.9 events/hr; oronasal, 5.3 events/hr; p  = 0.234) or median compliance (nasal, 7.3 hr/night; oronasal, 7.3 hr/night; p  = 0.961). Only four patients had 95th centile pressures that were at least 1.5 cm H2 O greater with oronasal masks. Oronasal masks do not systematically increase therapeutic CPAP requirements. Rather, a small subset of patients display significant differences in CPAP levels.